2000
DOI: 10.1161/01.res.87.8.677
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Estrogen Receptor Engagement Activates Endothelial Nitric Oxide Synthase via the PI3-Kinase–Akt Pathway in Human Endothelial Cells

Abstract: Abstract-17␤-Estradiol (E 2 ) is a rapid activator of endothelial nitric oxide synthase (eNOS). The product of this activation event, NO, is a fundamental determinant of cardiovascular homeostasis. We previously demonstrated that E 2 -stimulated endothelial NO release can occur without an increase in cytosolic Ca 2ϩ . Here we demonstrate for the first time, to our knowledge, that E 2 rapidly induces phosphorylation and activation of eNOS through the phosphatidylinositol 3 (PI3)-kinase-Akt pathway. E 2 treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
303
0
9

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 504 publications
(338 citation statements)
references
References 45 publications
20
303
0
9
Order By: Relevance
“…53 Cell membrane-localized ER has been demonstrated to interact with the regulatory subunit of PI3K and thereby to increase PI3K and Akt activity. 54,55 Such direct PI3K activation by a muristerone A-activated steroid hormone receptor is supported by the fact that we did not observe any transcriptional changes in the components of the PI3K/Akt pathway upon muristerone A treatment.…”
Section: Discussionsupporting
confidence: 56%
“…53 Cell membrane-localized ER has been demonstrated to interact with the regulatory subunit of PI3K and thereby to increase PI3K and Akt activity. 54,55 Such direct PI3K activation by a muristerone A-activated steroid hormone receptor is supported by the fact that we did not observe any transcriptional changes in the components of the PI3K/Akt pathway upon muristerone A treatment.…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, previous studies have shown that antioxidant supplementation with vitamins C and E (Plotnick et al, 1997) and red wine improves endothelial function. Alternatively, phytoestrogens could act directly on endothelial cell membrane, increasing nitric oxide generation by a non-genomic mechanism, as has been recently reported for estrogens (Haynes et al, 2000). Interestingly, a recent study in postmenopausal women with severe endothelial dysfunction of unknown origin did not show any effect of phytoestrogen tablets (80 mg/day) on vascular reactivity (Simons et al, 2000).…”
Section: Discussionmentioning
confidence: 82%
“…This does not seem to result from estradiol administration. Although estrogens are able to rapidly induce NO production in ECs without altering the expression of eNOS gene or protein (Caulin-Glasser et al 1997;Haynes et al 2000;Hisamoto et al 2001;Russel et al 2000;Lantin-Hermoso et al 1997), by a mechanism that involves PI3-kinase-dependent activation of Akt, neither estrogen receptors were expressed nor phospho-Akt expression was significantly changed, although Akt activation occurring in Sirt1 overexpression appears to be limited to insulinresistant conditions (Sun et al 2007). Fig.…”
Section: Discussionmentioning
confidence: 99%